Adenosine receptor A3 is a critical mediator in LPS-induced pulmonary inflammation - Wagner, Rosalyn; Ngamsri, Kristian-Christos; Stark, Stefanie; Vollmer, Irene; Reutershan, Joerg (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2010)
Adenosine receptor A3 (A3) regulates directed movement of polymorphonuclear cells (PMNs) to sites of inflammation and has been implicated as a relevant mediator in models of inflammatory diseases. Here, we sought to characterize the role of A3 in a murine model of lung inflammation. Initial studies revealed that pulmonary A3 transcript levels were elevated following LPS exposure in vivo. In addition, inhalation of LPS increased the accumulation of PMNs in wild-type and A3 -/- mice in all lung compartments. Pretreatment with the specific A3-agonist Cl-IB-MECA significantly decreased migration of PMNs into lung interstitium and alveolar air space of wild-type mice but not of A 3-/- mice. Lower PMN counts were associated with reduced levels of TNF-α and IL-6 in the alveolar space of wild-type mice that received Cl-IB-MECA. In addition, Cl-IB-MECA attenuated LPS-induced microvascular permeability in wild-type mice as assessed by the extravasation of Evans blue. In pulmonary microvascular endothelial cells, Cl-IB-MECA reduced LPS-induced cytoskeletal remodeling and cell retraction, consistent with a specific role of A3 for maintaining endothelial integrity. Migratory activity of human PMNs across an endothelial or epithelial monolayer was reduced when A3 was activated on PMNs. Studies in chimeric mice, however, revealed that Cl-IB-MECA required A3 on both hematopoietic and nonhematopoietic cells to reduce transmigration in vivo. Together, our results shed new light on the role of A3 in LPS-induced PMN trafficking in the lung and suggest pharmacological modulation of A3-dependent pathways as a promising approach in lung inflammation. Copyright © 2010 the American Physiological Society.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acute lung injury; Adenosine receptors; Polymorphonuclear leukocytes; Pulmonary circulation